Prolonged COVID-19 infection in a child with lymphoblastic non-Hodgkin lymphoma: which is the best management?. Issue 6 (December 2022) - Gattuso, Giovanna; Schiavello, Elisabetta; Oltolini, Chiara; Biassoni, Veronica; Terenziani, Monica; Chiaravalli, Stefano; Podda, Marta Giorgia; Meazza, Cristina; Luksch, Roberto; Ferrari, Andrea; Casanova, Michela; Sironi, Giovanna; et al.
During the coronavirus disease 2019 (COVID-19) pandemic, oncologists have managed patients at higher risk of having a severe course of this infection. This raises new questions about their correct management, as well as the difficulty of distinguishing tumor/treatments complications from those related to COVID-19. We report a case of an 11-year-old boy undergoing treatment for T-cell lymphoblastic lymphoma who experienced a prolonged COVID-19 course. Oncologic therapy was continued without significant changes compared to the initially planned treatment. No relevant complications occurred. COVID-19 convalescent plasma was administered, resulting in a positive antibody titer after 24 days.